(untitled) (Architecture Image Studies, 2026)
HVAC systems represent the largest proportion of energy consumption in buildings, necessitating the analysis and evaluation of alternative technologies to achieve energy efficiency and sustainability. This study analyzes and compares the thermal and energy performance of three common air conditioning systems used in building applications: Variable Refrigerant Flow (VRF) systems, Air-cooled Chiller systems, and packaged DX system. The thermal simulation software Design Builder was used to model the behavior of these three systems Inside the Deanship building of the College of Engineering at the University of Nineveh in Mosul, under continuous climatic conditions. Two types of simulations were performed for the building at different WWR ratios (10, 20, 30, 40, 50, 60) %. The addition of (XPS Extruded Polystyrene - CO2 Blowing) type insulation to the walls and roofs with a thickness of (1, 2, 3, 4, 5, 6) centimeters was also tested. In all these cases, the building’s energy consumption was tested using the above systems. The summer simulation of the (cooling load) for air conditioning systems was conducted from (20 June to 22 September), while the winter simulation of the (heating load) was conducted from (21 December to 20 March). Results showed that VRF systems achieved energy savings of 50% in summer and 60% in winter compared to Air-cooled Chiller System, VRF systems also achieved savings of 18% in summer and 15% in winter compared to Packaged DX System.